2000
DOI: 10.1038/modpathol.3880216
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of p53 Mutations in ThinPrep-Processed Fine Needle Breast Aspirates with Surgically Resected Breast Cancers

Abstract: Mutations of the p53 gene are one of the most common genetic changes found in cancer; their presence may be prognostic and even influence treatment for breast cancer. In this study, we investigated whether DNA could be extracted from the residual cells left in ThinPrep-processed breast fine-needle aspirates and whether p53 gene changes could be detected in the DNA. The results were then correlated with DNA extracted from the matched formalin-fixed, paraffin-embedded, surgically resected breast cancer when avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
10
0
3
Order By: Relevance
“…However, studies have reported that, if LBP is used, residual samples or floating cells preserved in preservation solution can be used as goodquality source materials for molecular tests; good-quality DNA has been successfully extracted from LBP samples stored for more than a year [23,24]. In our study, the longest sample storage period was 13 months; and there was no significant difference in the quality of DNA between this sample and samples stored for shorter periods.…”
Section: Discussionmentioning
confidence: 49%
“…However, studies have reported that, if LBP is used, residual samples or floating cells preserved in preservation solution can be used as goodquality source materials for molecular tests; good-quality DNA has been successfully extracted from LBP samples stored for more than a year [23,24]. In our study, the longest sample storage period was 13 months; and there was no significant difference in the quality of DNA between this sample and samples stored for shorter periods.…”
Section: Discussionmentioning
confidence: 49%
“…Future studies should be large (which would allow assessment of effect modification by factors, such as menopausal status), should assess both p53 immunopositivity and mutation status, and should use state-of-the-art methods for p53 mutation detection. Although the present report involved the use of paraffin-embedded breast tissue, the analyses described herein can also be done on tissue obtained from needle biopsies and on cells obtained from fine-needle aspirates of the breast, both of which are done increasingly commonly nowadays (42,(51)(52)(53). If confirmed, the findings reported here might facilitate the development of new approaches both to the detection of women at increased risk of breast cancer and to their clinical management [e.g., by enabling chemoprevention or therapy to restore p53 function (54) to be targeted to specific subgroups of women].…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, immunocytochemistry and molecular analysis have been successfully applied to TP processed specimens. 14,15 HER2 gene amplification in human breast cancers was first described by Slamon et al in 1987. 4 Overexpression of HER2 protein results from gene amplification and occurs in 20-30% of invasive human breast cancer.…”
Section: Discussionmentioning
confidence: 99%